Studi Explorasi Permasalahan Kesehatan di Desa Pesaren Kecamatan Warungasem Kabupaten Batang Melalui Pendekatan Community Needs Diagnosis - Rr. Vita Nur Latif; Nor Istiqomah (Pena Medika Jurnal Kesehatan, 2013)
Background  :  Community  empowerment  requires  the  independence  efforts  of  society,  and  sensitizing  the community  itself is  expected  to  recognize  and  identify  the  problems  that  exist in  the  community,  especially health problems. The essence of community empowerment through community needs diagnosis effort is able to independently identify, exemine issues, prioritize problems, make a plan of intervention based on   issues as  resolving  disputes.  This  is  what  underlies  the  implementation  of  this  research  entitled  Explorations  of Health  Problems  in  Pesaren,  Kecamatan  Warungasem,  District  of  Batang  through  Community  Needs diagnosis approach. Methods : The study using a qualitative case study approach. The collection of data through observation, in- depth  interviews  and  FGD  (Focus  Group  Discussion)  to  explore  health  issues  through  community  needs diagnosis. Informants of this study consisted of elements of community leaders, head of the health center and village midwives related. Results  :  Based  on  the  results  of  the  study  identified  several  health  problems  in  Pesaren  subdistrict Warungasem  Batang is  scabies,  Acute  respiratory  tract  infections  (ISPA), dermatitis,  cephalgia,  Diarrhea. Based on Hanlon mathematical calculation,  scabies is a priority issue that must be resolved, by  a score of 600. This calculation is based on severity of problems (severity), the number of people affected (prevalence), the increase in disease rate (rate of increase), community desire (degree of unmeet needs), social advantages if  the  problem  is  resolved  (social  benefits),  community  concerns  about  the  issue  (public  concern),  the availability of technology (technical feasibility), the resources (resources availability), and political support (political climate). Keywords : health issues, community needs diagnosis